Binding Profiles of Self‐Assembled Supramolecular Cages from ESI‐MS Based Methodology. Issue 12 (31st January 2018) - Bravin, Carlo; Badetti, Elena; Puttreddy, Rakesh; Pan, Fangfang; Rissanen, Kari; Licini, Giulia; Zonta, Cristiano
Abstract: Confined molecular environments have peculiar characteristics that make their properties unique in the field of biological and chemical sciences. In recent years, advances in supramolecular capsule and cage synthesis have presented the possibility to interpret the principles behind their self‐assembly and functions, which has led to new molecular systems that display outstanding properties in molecular recognition and catalysis. Herein, we report a rapid method based on ESI‐MS to determine the binding profiles for linear saturated dicarboxylic acids in a series of different cages. The cages were obtained by self‐assembly of modified tris(pyridylmethyl)amine (TPMA ) complexes and diamines chosen to explore variations in their size and flexibility. This methodology has provided information on how small changes in the structures of the host and guest can contribute to recognition events. Moreover, it was possible to study molecular systems that contain paramagnetic metals, which are not suitable for classical binding‐constant determination by 1 H NMR spectroscopy. Abstract : I spy with ESI ! ESI‐MS can be used as rapid method to determine the binding profiles for linear saturated dicarboxylic acid guests in a series of self‐assembled supramolecular cages (see figure).